Perselisihan Keluarga Akibat Pembagian Warisan Keluarga - Tamaaulina Br. Sembiring; Zavfirah Alya; Sinta Grace Ika Sianturi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Family disputes over inheritance are a common social and legal issue in Indonesian society, often leading to long-term conflicts and even legal battles. This situation is influenced by the complex legal system of inheritance in Indonesia, which is pluralistic and includes Western civil law, Islamic law, and customary law. It is further complicated by social, cultural, economic, and psychological factors among the heirs. This study aims to analyze the causes of family disputes in inheritance distribution and examine the role of law in providing certainty, fairness, and benefits for all parties involved. The research method used is normative legal research with a jurisprudential approach, through the study of relevant legal regulations, legal doctrines, and court decisions. The findings show that inheritance disputes are generally caused by unfair distribution of assets, differing interpretations of law, conflicts between customary law, religious law, and national law, as well as poor communication and lack of transparency within the family. Therefore, resolving inheritance disputes requires not only the enforcement of law in a normative manner, but also non-litigious approaches such as mediation, family consultation, and increased legal awareness to maintain family harmony and legal certainty.